2021
DOI: 10.1021/acsanm.1c01126
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Reduced Graphene Oxide Covalently Coupled with Graphitic Carbon Nitride/Sulfur-Doped Graphitic Carbon Nitride Heterojunction Nanocatalysts for Photoreduction and Degradation of 4-Nitrophenol

Abstract: 4-Nitrophenol (4-NP) is a high-priority industrial pollutant and is known to cause adverse effects to the human body. Owing to this, detoxification of water contaminated with 4-NP is highly essential. The photocatalytic degradation of 4-NP is considered an efficient method. However, for this purpose, mostly expensive reagents that can cause adverse effects on the environment are used. Therefore, for the treatment of 4-NP contaminated water, an eco-friendly method is considerably required. To meet this requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…Additionally, the quantum confinement effect, up-conversion, and bright photoluminescence of quantum dots are appealing to harvest a major fraction of light. Indeed, extremely high numbers of reports are available on the use of carbon-based materials coupling with inorganic semiconductors to make 0D/2D, 0D/3D, 2D/2D, 2D/3D, and 3D/3D hybrids to improve photocatalytic properties. Among them, 2D sheets of graphene and graphene oxide have proven to be the most promising due to their 2D nature and excellent optoelectronic properties. Sticking to the scope of this review, we will revisit the scope of 2D carbon-based materials to integrate with g-C 3 N 4 based semiconductors.…”
Section: Carbon Nitride–carbon 2d/2d Vdw Structuresmentioning
confidence: 99%
“…Additionally, the quantum confinement effect, up-conversion, and bright photoluminescence of quantum dots are appealing to harvest a major fraction of light. Indeed, extremely high numbers of reports are available on the use of carbon-based materials coupling with inorganic semiconductors to make 0D/2D, 0D/3D, 2D/2D, 2D/3D, and 3D/3D hybrids to improve photocatalytic properties. Among them, 2D sheets of graphene and graphene oxide have proven to be the most promising due to their 2D nature and excellent optoelectronic properties. Sticking to the scope of this review, we will revisit the scope of 2D carbon-based materials to integrate with g-C 3 N 4 based semiconductors.…”
Section: Carbon Nitride–carbon 2d/2d Vdw Structuresmentioning
confidence: 99%
“…25 Non-metallic element decoration (O, halogen elements, S, B, and P) is one of the viable solutions, as it may change the electrical properties and enhance the visible light-harvesting potential while still maintaining charge transference. [26][27][28] For example, Liu fabricated Sengineered g-C 3 N 4 by reacting g-C 3 N 4 with H 2 S as a S source at 449 C, which demonstrated signicantly higher photocatalytic H 2 evaluation ability than undoped g-C 3 N 4 . 29 Hong et al described that mesoporous SCN showed thirty times greater H 2 generation activity than pure g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous reports, in this method, a nonfluorescent TA solution interacts with the photogenerated OH˙ radical to form fluorescent 2-hydroxyterephthalic acid (TAOH), which was detected by the PL technique. 48 Here, the fluorescence intensity of TAOH can be related to the OH˙ radical generation in the photoreaction. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For reference, rGO, g-C 3 N 4 , and α-Fe 2 O 3 were also prepared by following the aforementioned process without adding “urea and amorphous iron oxide,” “GO and amorphous iron oxide,” and “GO and urea.” NrGO was prepared by taking GO and urea as a nitrogen source using the thermal annealing process. 48 Scheme 1 depicts a schematic representation of the synthesis procedure for NGCF hybrid nanocomposites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation